ZASADA PRAWDY FORMALNEJ W POLSKIM CYWILNYM PRAWIE PROCESOWYM A ROZUMOWANIA NIEMONOTONICZNE - Trepczyński, Marcin (Zeszyty Prawnicze, 2016)
The Principle of Formal Truth in the Polish Civil Procedural Law and Non-monotonic Reasoning Summary This paper analyses the implementation of the formal truth principle in the Polish civil procedural code in the light of non-monotonic reasoning. The author starts by presenting the concept and applications of non-monotonic reasoning, and the formal truth principle and its place in Polish civil procedure. Next he examines the conditions in which non-monotonicity is admissible in civil court reasoning. While legal reasoning may generally be regarded as non-monotonic due to the assumptions it employs and treats as defensible, the author’s observations on the basis of selected civil law cases lead him to the conclusion that the use of the formal truth principle as a viable instrument in law simply forces courts to make non-monotonic inferences. In other words, adopting this principle means accepting non-monotonic reasoning, or even more: if the court keeps to the formal truth principle it is using one of the types of non-monotonic logic.